Estetica della Resistenza : Corso Superiore di Arte Visiva. - Pinto, Roberto; Fondazione Antonio Ratti, Como (Como, : Fondazione Antonio Ratti, 2005)
Wilkinson, Thomas ; Wedell, Juliane ; Pei-Mun Tsang, James ; Studio Trickster ; Trevisani, Luca ; Rivadeneira, Karen Miranda ; Senatore, Marinella ; Pak, June ; Passarini, Annapaola ; et al.
Fondazione Antonio Ratti, Como (?), July 21 - September 4, 2005
kunstcatalogus